2020
DOI: 10.1002/ijfe.2231
|View full text |Cite
|
Sign up to set email alerts
|

The Oil Price‐Macroeconomic fundamentals nexus for emerging market economies: Evidence from a wavelet analysis

Abstract: This study uses the (partial) cross wavelet analysis and the phase difference to decompose the time frequency effects of oil prices on major aggregate macroeconomic fundamentals (real effective exchange rate index, interest rate yield spread and stock market index) of emerging market economies, aiming to discern the direction of the lead-lag relationship between these variables at different time scales over the period December 1987 to April 2017. Our results suggest that there is a strong coherence between oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…Previous studies have indicated that the appreciation of the US dollar will favorably improve the trade balances of oil-exporting countries and hence, lead to an increase in their terms of trade. This improvement in terms of trade is called the "wealth effect" that leads to increases in the price of oil (Tiwari et al, 2020a(Tiwari et al, , 2020bTaghizadeh-Hesary et al, 2019). At the same time, however, this increase in oil prices causes a supply shock to the oil-importing countries, which may be forced to reduce the volume of their imported crude oil (Reboredo, 2012).…”
Section: Theoretical Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have indicated that the appreciation of the US dollar will favorably improve the trade balances of oil-exporting countries and hence, lead to an increase in their terms of trade. This improvement in terms of trade is called the "wealth effect" that leads to increases in the price of oil (Tiwari et al, 2020a(Tiwari et al, , 2020bTaghizadeh-Hesary et al, 2019). At the same time, however, this increase in oil prices causes a supply shock to the oil-importing countries, which may be forced to reduce the volume of their imported crude oil (Reboredo, 2012).…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Consequently, international investors will tend to invest in real assets such as oil as a hedge fund (Akram, 2009). Moreover, Tiwari et al (2020aTiwari et al ( , 2020b state that:…”
Section: Directionality From Interest Rate To Oil Pricementioning
confidence: 99%
See 1 more Smart Citation
“…Z. Chen et al (2021) used a VECM to study the price discovery of the Chinese agricultural futures market. Apart from traditional measurement methods, multidisciplinary methods have also been used to measure price discovery, such as the wavelet transform (Okorie & Lin, 2020; Tiwari et al, 2020), the hidden Markov model (De Blasis, 2020), information theory (Fiedor, 2014), and the TOP method (Wang et al, 2017), among others. To quantitatively describe the price discovery ability of financial markets, we plan to measure the lead–lag effect of the financial sequence using the TOP method proposed by Sornette and Zhou (2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Generally speaking, Granger causality analysis, cointegration test, and the vector error correction model are the most commonly used methods to explore price discovery functions and lead-lag effects. Wavelet transform is also favored by many scholars to conduct lead-lag analysis (Okorie & Lin, 2020;Tiwari et al, 2020). However, considering that the lead-lag relationship is likely to be dynamic and nonlinear, the nonparametric TOP method proposed by Sornette and Zhou (2005) is applied in this study for analysis.…”
mentioning
confidence: 99%